1997
DOI: 10.1111/j.2042-3306.1997.tb03137.x
|View full text |Cite
|
Sign up to set email alerts
|

Matrix metalloproteinases 2 and 9 in equine synovial fluids

Abstract: Summary Matrix metalloproteinases (MMPs) may be important in the destruction of cartilage seen in equine osteoarthritis and may be detectable in synovial fluid. Synovial fluids were obtained from normal equine joints and from joints of horses with aseptic and septic joint diseases. The total MMP gelatinase enzyme activities were measured by gelatin zymography and image analysis of the gels. The bioactivity of gelatinase in synovial fluid was determined by a gelatin degradation ELISA. Potential MMP‐2 & MMP‐9 mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

10
64
3

Year Published

2000
2000
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(77 citation statements)
references
References 19 publications
10
64
3
Order By: Relevance
“…The occurrence of the active form of the MMP-9 monomer was associated to the presence of a degenerative process. These results are in agreement with the data from Clegg et al [9] who found a rise in MMP-9 activities in a broad range of aseptic joint diseases. In osteoarthritic joints, Brama et al [3] also found the MMP-9 activity was nearly twice as high as in normal joints, but, in OCD joints, MMPs activity was not significantly different from normal control joints.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…The occurrence of the active form of the MMP-9 monomer was associated to the presence of a degenerative process. These results are in agreement with the data from Clegg et al [9] who found a rise in MMP-9 activities in a broad range of aseptic joint diseases. In osteoarthritic joints, Brama et al [3] also found the MMP-9 activity was nearly twice as high as in normal joints, but, in OCD joints, MMPs activity was not significantly different from normal control joints.…”
Section: Discussionsupporting
confidence: 83%
“…This assay is highly specific, because it is based on a direct enzyme-substrate interaction, and gives information on the molecular weights of the enzymes (latent or active form). The gelatinases found in this study were comparable to those reported by Clegg et al [9] from aseptic and septic joint samples.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Matrix metalloproteinases (MMPs) are a family of nine or more highly homologous Zn(++)-endopeptidases that collectively cleave most, if not all, of the constituents of the extracellular matrix (Birkedal-Hansen et al 1993). They are important in remodelling events and the migration of cells through the extracellular matrix (Birkedal-Hansen et al 1993;Allan et al 1995;Clegg et al 1997;Koolwijk et al 1995) and also in tumour growth and metastasis, promoting the migration and invasion of cells (Sier et al 2000).…”
mentioning
confidence: 99%